Implementasi Perma Nomor 1 Tahun 2015 tentang Pelayanan Terpadu Sidang Keliling dalam Sidang Itsbat Nikah Terpadu Tahun 2021 - Ninda Sari Sri Rejekinah; Encep Abdul Rojak (UNISBA Press, 2022)
Abstract. Marriage is a teaching in Islam which is based on the Qur'an and hadith. Marriage in Indonesia requires registration of marriages. By registering a marriage, the achievement of administrative order and marriage becomes clear. Itsbat marriage is one way for those whose marriages have not been recorded, with the marriage itsbat of marriages that have been carried out obtaining legal legality and the marriage becomes clear. As for what is meant by integrated marriage itsbat, namely, the marriage itsbat trial which is carried out jointly and in collaboration with several related agencies. The integrated marriage itsbat carried out by the Religious Courts is regulated in Perma Number 1 of 2015 concerning Integrated Services for Mobile Courts. Perma Number 1 of 2015 has a goal to improve services in the field of law and help the community, especially people who have limited costs, distance, and time in obtaining their civil rights. In this study, the authors formulate a problem regarding the procedure for integrated marriage itsbat contained in Perma Number 1 of 2015, as well as the purpose of this study to answer the formulation of the problem. The method used in this study uses a qualitative method with a normative juridical approach and data analysis techniques are carried out using conceptual and interactive analysis techniques. The results and conclusions in this study are the implementation of the integrated marriage itsbat trial carried out by the Purwakarta Religious Court in accordance with the terms and conditions of Perma Number 1 of 2015, and its implementation can be said to be effective and successful in applying the principles of simple, fast, and low cost. Abstrak. Perkawinan merupakan ajaran dalam Islam yang berdasar pada Al-Qur’an dan hadits. Perkawinan di Indonesia mengharuskan dilakukannya pencatatan perkawinan. Dengan tercatatnya suatu perkawinan maka, tercapainya tertib administrasi dan perkawinannya menjadi jelas adanya. Itsbat nikah merupakan salah satu jalan bagi yang perkawinannya belum tercatat, dengan dilakukannya itsbat nikah perkawinan yang telah dilakukan mendapat legalitas hukum dan perkawinannya menjadi jelas adanya. Adapun yang dimaksud dengan itsbat nikah terpadu yaitu, sidang itsbat nikah yang dilakukan secara bersama-sama dan bekerjasma dengan beberapa instansi terkait. Itsbat nikah terpadu yang dilakukan oleh Pengadilan Agama diatur dalam Perma Nomor 1 Tahun 2015 Tentang Pelayanan Terpadu Sidang Keliling. Perma Nomor 1 Tahun 2015 memilki tujuan untuk meningkatkan pelayanan di bidang hukum dan membantu masyarakat khususnya masyarakat yang memiliki keterbatasan biaya, jarak, dan waktu dalam memperoleh hak keperdataannya. Dalam penelitian ini penulis merumuskan masalah mengenai prosedur itsbat nikah terpadu yang terdapat dalam Perma Nomor 1 Tahun 2015, serta tujuan dalam penelitian ini untuk menjawab rumusan masalah. Metode yang digunakan dalam penelitian ini menggunakan metode kualitatif dengan pendekatan yuridis normatif dan teknik analisis data dilakukan dengan teknik analisis konsep dan interaktif. Adapun hasil dan simpulan dalam penelitian ini yaitu Pelaksanaan sidang itsbat nikah terpadu yang dilaksanakan oleh Pengadilan Agama Purwakarta telah sesuai dengan syarat serta ketentuan Perma Nomor 1 Tahun 2015, dan pelaksanaanya dapat dikatakan efektif dan berhasil menerapkan asas sederhana, cepat, dan biaya ringan.